Designing an Infotainment System for Electric Motorcycles: Enhancing User Experience for Urban Commuting without Compromising Safety - Kumnova, Getoar; Imsirovic, Adis (My University, 2019)
The Master thesis was done in collaboration with Regent Motorcycles which is a company started within ANNEVO’s innovation studio, situated in Gothenburg. The thesis was conducted to concretize what difficulties, requirements and needs motorcyclists have when driving, more specifically in urban areas concerning an electric motorcycle. This would be done by compiling a list consisting of requirements and user stories (which essentially are desired features). This list would be compiled based on the gathered information and knowledge throughout the project. The list would also become the underlying basis for a second project goal, which was to produce an infotainment system concept that would essentially embody the defined product requirements and user needs. The master thesis resulted in an infotainment concept which called MotoRide Infotainment and can be interacted through a keypad at the left handlebar, eight-inch touch display or a Bluetooth connected headset. Having the display gives possibility to visually display various information and entertainment features. The information and entertainment consist of a music player, navigation, GPS and phone communication. By wirelessly connecting a smartphone through Bluetooth, it is possible access the smartphone’s music and communication capabilities. What functionality is accessible depends if the motorcycle is in drive- or neutral mode to prevent the rider from exceeding mental workload. The infotainment system is designed to simplify riding in urban areas by offering real time information about present traffic situation and giving suggestions on alternative routes to avoid traffic jams based on destination set in the navigation. The infotainment system has the option of always being connected to the internet as well, independently from a connected smartphone. The Motoride concept fulfilled the project goals which was to provide guidelines for how an infotainment system should be designed for an electric motorcycle that is meant for urban commuting. The concept aims to provide the functionalities that the modern motorcyclist expects and remove the need of using a smartphone while riding. Finding the balance between the safety aspect is essential. The number of features should not infringe on the rider’s ability to maintain awareness of their surroundings and should be complemented with a user interface that enables the rider to stay in full control. Even if the MotoRide concept was designed for the target group of Regent’s retro-designed motorcycle in terms of user experience and needs, they are still based on the needs of motorcycle riders which means that the infotainment design guidelines, together with the concept, still provides a suggestion for how to keep riders satisfied and safe at the same time.